Synthesis of Dendritic Tryptophan Derivatives and Investigation on Dendritic Effects of their Fluorescence and Reactivity - He, Dongsheng; He, Gu; Guo, Li (Letters in Organic Chemistry, 2011)
Two series of dendritic tryptophan derivatives have been synthesized and characterized, their emission spectra in different solvents and the reactivity of tryptophan were investigated and compared. There was a progressive shielding effect of the tryptophan in the emissive wavelengths of dendrimers increased with the size or generation of the dendritic shell.
Keywords: hydrophobe